Learning Japanese interactional particles through a usage-based and concept-based language instruction. (24th October 2022) - Masuda, Kyoko
Abstract : The purpose of the current study is two-fold. First, this paper aims to uncover the three-year acquisition process of three interactional particles, ne, yo, and yone by three Chinese-speaking learners of Japanese in a corpus. Among the three particles, yone appeared the latest after one year of study abroad, and the learners progressed in their usage by trying to share epistemic stance and assessments by using yone. However, understanding the epistemic stance for the speaker's world is challenging. Second, this paper supports the integration of usage-based approaches and sociocultural theory. For teaching interactional particles effectively in the classroom, understanding of the role of intersubjectivity in discourse is crucial. This paper proposes three sets of schematic visual representations for core meanings of ne, yo, and yone, which is essential for concept-based language instruction.